The Smith-Lemli-Opitz syndrome - Kelley, R. (BMJ Group, 2000)
The Smith-Lemli-Opitz syndrome (SLOS) is one of the archetypical multiple congenital malformation syndromes. The recent discovery of the biochemical cause of SLOS and the subsequent redefinition of SLOS as an inborn error of cholesterol metabolism have led to important new treatment possibilities for affected patients. Moreover, the recent recognition of the important role of cholesterol in vertebrate embryogenesis, especially with regard to the hedgehog embryonic signalling pathway and its effects on the expression of homeobox genes, has provided an explanation for the abnormal morphogenesis in the syndrome. The well known role of cholesterol in the formation of steroid hormones has also provided a possible explanation for the abnormal behavioural characteristics of SLOS.   Keywords: Smith-Lemli-Opitz syndrome; cholesterol metabolism; 7-dehydrocholesterol reductase; clinical history; management